ANCAMAN DAN TANTANGAN PROFESI AKUNTAN MENGHADAPI REVOLUSI DIGITAL DI ERA SOCIETY 5.0 - Dina Alafi Hidayatin; Risma Susanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
The emergence of the era of society 5.0, marked by the rapid digital world and the domination of robotics and artificial intelligence, has disrupted almost all fields of life, including the field of accounting. This era has forced people to innovate and change if they don't want to be left behind. Although in general it brings progress, on the other hand it also brings challenges and threats to the accounting profession. Then accountants must have a strategy to face the challenges and threats of the accounting revolution that can be implemented, such as investing in the development of digital skills, implementing new technology prototypes while learning by doing, education based on international certification, responsive to changes in industry, business and technological developments, and curricula and learning based on human-digital skills. The purpose of this research is to find out the challenges and threats to the accounting profession in facing the digital revolution in the era of society 5.0. This research is a descriptive research, using literature study method. Conclusions are drawn based on a collection of expert opinions, both accounting experts and experts in the field of information technology